Transport and retention of carbon-based engineered and natural nanoparticles through saturated porous media - Hedayati, Maryeh; Sharma, Prabhakar; Katyal, Deeksha; Fagerlund, Fritjof (Journal of nanoparticle research : an interdisciplinary forum for nanoscale science and technology, 2016)
Carbon-based engineered nanoparticles have been widely used due to their small size and unique physical and chemical properties. At the same time, the toxic effects of these nanoparticles on human and fish cells have also been observed; therefore, their release and distribution into the surface and subsurface environment is a subject of concern. The aim of this research is to evaluate and compare the transports and retentions of two types of engineered nanoparticles (multiwalled carbon nanotubes and C 60 ) and the natural carbon nanoparticles collected from a fire accident. Several laboratory experiments were conducted to observe the transport behavior of nanoparticles through a column packed with silica sand. The column experiments were intended to monitor the effect of ionic strength on transport of nanoparticles as a function of their shapes. It was observed that the mobilities of both types of engineered nanoparticles were reduced with the increasing ionic strength from 1.34 to 60 mM. However, at ionic strengths up to 10.89 mM, spherical nanoparticles were more mobile than cylindrical nanoparticles, but the mobility of the cylindrical nanoparticles became significantly higher than spherical nanoparticles at the ionic strength of 60 mM. In comparison with natural fire-born nanoparticles, both types of engineered nanoparticles were much less mobile under the selected experimental condition in this study. Furthermore, inverse modeling was used to calculate parameters such as attachment efficiency, the longitudinal dispersivity, and capacity of the solid phase for the attachment of nanoparticles. The results indicate that the combination of the shape and the solution chemistry of the NPs are responsible for the transport and the retention of nanoparticles in natural environment; however, fire-burned nanoparticles can be highly mobile at the natural groundwater chemistry.